2002
DOI: 10.1136/bmj.325.7374.1202
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and cardiovascular disease: evidence on causality from a meta-analysis

Abstract: Objective To assess whether the association of serum homocysteine concentration with ischaemic heart disease, deep vein thrombosis and pulmonary embolism, and stroke is causal and, if so, to quantify the effect of homocysteine reduction in preventing them. Design Meta-analyses of the above three diseases using (a) 72 studies in which the prevalence of a mutation in the MTHFR gene (which increases homocysteine) was determined in cases (n=16 849) and controls, and (b) 20 prospective studies (3820 participants) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

51
1,224
11
43

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,728 publications
(1,329 citation statements)
references
References 21 publications
51
1,224
11
43
Order By: Relevance
“…Of particular interest, extensive evidence has led to a number of meta-analyses reporting a strong association between this polymorphism and CVD, particularly stroke (73)(74)(75)(76) . It has been estimated that individuals with the MTHFR 677TT polymorphism have a 14-21 % increased risk of CHD (75,77,78) .…”
Section: Riboflavin C 1 Metabolism and Cvd Riskmentioning
confidence: 99%
“…Of particular interest, extensive evidence has led to a number of meta-analyses reporting a strong association between this polymorphism and CVD, particularly stroke (73)(74)(75)(76) . It has been estimated that individuals with the MTHFR 677TT polymorphism have a 14-21 % increased risk of CHD (75,77,78) .…”
Section: Riboflavin C 1 Metabolism and Cvd Riskmentioning
confidence: 99%
“…The MTHFR 677C T polymorphism previously received much attention as the main genetic determinant of homocysteine (10) and is also independently associated with an increased risk of CVD and particularly stroke (1,2,20,21) . Several meta-analyses to date have demonstrated an increased risk of CVD in individuals with the TT genotype compared to those without this genetic variant (1,2,(20)(21)(22) (Table 1).…”
Section: Association Between the Mthfr 677c T Polymorphism And Cvd Riskmentioning
confidence: 99%
“…According to a meta-analysis, a decrease in serum homocysteine by 3 mmol l À1 should reduce the risk of ischemic heart disease deep vein thrombosis and stroke by 16, 25 and 24%, respectively. 24 Such a reduction in homocysteine would be achievable by folic acid supplementation of 0.8 mg day À1 . 25 Other studies, however, have suggested that folic acid intervention, in the presence and absence of vitamin B 6 , does not lower the risk of recurrent cardiovascular disease or death after acute myocardial infarction.…”
Section: Cardiovascular Diseasementioning
confidence: 99%